Video Analytics for Audience Measurement First International Workshop, VAAM 2014, Stockholm, Sweden, August 24, 2014. Revised Selected Papers - Distante, Cosimo; Battiato, Sebastiano; Cavallaro, Andrea (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2014)
This book constitutes the refereed contest reports of the 1st International Workshop, VAAM 2014, held in Stockholm, Sweden, in August 2014. The 10 revised full papers presented were carefully reviewed and selected from 13 submissions. The aim of this workshop is to provide an overview of state of the art methods for audience measurements in retail and Digital Signage, end-users attraction, and stimulate the creation of appropriate benchmark dataset to be used as reference for the development of novel audience measurement algorithms. Papers are invited under the following topics: demographics and modeling consumer behaviour.